Identification of immunostimulatory activities and active compounds from sequentially extracted fractions of rhizosphere fungal fermentation broth of Atractylodes macrocephala Koidz. rhizomes - Xie, Yuxin; Lin, Na; Song, Pingping; Ni, Xiangyan; Wang, Yakun; Huang, Peng; Han, Zhili; Wang, Dianlei; Sun, Nianxia (Frontiers in Pharmacology, 2024)
IntroductionPharmacological studies have shown that the rhizome of Atractylodes macrocephala Koidz. (Compositae), commonly known as atractylodes macrocephala rhizome (AMR), can modulate immunity. Nevertheless, its resources have been largely depleted, and the pharmacological activity of artificial AMR is relatively modest. We hypothesized that the fermented crude extracts of the rhizosphere fungi of AMR would have similar immunomodulatory effects since the metabolites generated by these fungi are similar to those of the host plant given their long-term synergistic evolution.MethodsRhizosphere fungi were isolated from the rhizosphere soil of AMR and cultured to produce the secondary metabolites. These metabolites were then sequentially extracted with four solvents of increasing polarities (petroleum ether, ethyl acetate, n-butanol, and water). The in vitro immunomodulatory activities of the metabolite extracts were evaluated by cell proliferation capacity, cell phagocytosis activity, NO secretion capacity, cell morphology changes, and cytokine (TNF-α, IL-1β and IL-6) secretion capacity in RAW264.7 macrophage cells. The biologically active secondary metabolites produced by the rhizosphere fungi were identified using ultrahigh-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF-MS).ResultsThree rhizosphere fungi, namely Penicillium (MK-1), Penicillium glaucoroseum (MN-1), and Purpureocillium lilalium (MG-1), were isolated from the rhizosphere soil of AMR. The assays for cell proliferation capacity, cell phagocytosis activity, and NO secretion capacity showed that all metabolite extracts exhibited in vitro immunomodulatory activities. The crude extracts of MG-1 exhibited the highest levels of in vitro immunomodulatory activities compared to the other extracts. Furthermore, it was demonstrated that the fermented extracts of MG-1 could facilitate immunological enhancement in vitro by altering the cellular morphology in the resting state and increasing the secretions of TNF-α, IL-1β, and IL-6. Meanwhile, there was no observable endotoxin contamination. The metabolite profiling of MG-1 by UHPLC-Q-TOFMS revealed the presence of several compounds with established immunoreactive activities, including L-arginine, prostaglandin I2, deoxyguanosine, bestatin, and osthole.DiscussionThe present study demonstrated that the metabolite extracts of the rhizosphere fungi isolated from the rhizosphere soil of AMR exhibited in vitro immunoreactive activities and that these rhizosphere fungi could produce several bioactive metabolites. The crude extracts of the rhizosphere fungi may hence extend the medicinal utility of AMR and provide a basis for further development of natural plant-based immunomodulators.